2020
DOI: 10.3847/1538-4357/ab6a94
|View full text |Cite
|
Sign up to set email alerts
|

Global Chemistry and Thermal Structure Models for the Hot Jupiter WASP-43b and Predictions for JWST

Abstract: The James Webb Space Telescope (JWST) is expected to revolutionize the field of exoplanets. The broad wavelength coverage and the high sensitivity of its instruments will allow characterization of exoplanetary atmospheres with unprecedented precision. Following the Call for the Cycle 1 Early Release Science Program, the Transiting Exoplanet Community was awarded time to observe several targets, including WASP-43b. The atmosphere of this hot Jupiter has been intensively observed but still harbors some mysteries… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
144
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 91 publications
(155 citation statements)
references
References 171 publications
(216 reference statements)
11
144
0
Order By: Relevance
“…One noteworthy tentative prediction from our simplified WASP-43b simulation is that the night side will emit overall very little flux in the near-to mid-infrared ranges (Figure 7) -even compared to predicted spectra derived from cloudy GCMs that display full superrotation in their simulations (Parmentier et al 2016). This prediction will be testable with observations by JWST/MIRI (Bean et al 2018;Venot et al 2020). There are some shortcomings in these tentative predictions as we will show in the next section.…”
Section: The Effects Of Magnetic Field On Deep Wind Jets and The Observable Atmospheresupporting
confidence: 63%
See 4 more Smart Citations
“…One noteworthy tentative prediction from our simplified WASP-43b simulation is that the night side will emit overall very little flux in the near-to mid-infrared ranges (Figure 7) -even compared to predicted spectra derived from cloudy GCMs that display full superrotation in their simulations (Parmentier et al 2016). This prediction will be testable with observations by JWST/MIRI (Bean et al 2018;Venot et al 2020). There are some shortcomings in these tentative predictions as we will show in the next section.…”
Section: The Effects Of Magnetic Field On Deep Wind Jets and The Observable Atmospheresupporting
confidence: 63%
“…WASP-43b appears thus to be a planet that is well suited for comparing different models with each other (see also e.g. Venot et al (2020)). The significance of the lower-boundary treatment has been recently highlighted again for GJ 1214b, a fast rotator (P rot = 1.5 days), where it was found that the dynamics in the deep atmosphere significantly impact the observables in the upper atmosphere (Wang & Wordsworth 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations